Goats and Goddesses. Digital Approach to the Religioscapes of Atargatis and Allat - Kubiak-Schneider Aleksandra; Mazurek Sebastien (Open Archaeology)
This study presents the use of a new methodological tool for studying the history of ancient religions through social and geographical aspects. NodeGoat, an open-source online software, helps in creating maps and social network charts as well as visualizing the data on a time axis. The study of worshippers of Allat and Atargatis in the Near East and beyond in the Hellenistic and Roman periods focuses more on the people and their role in creating the religioscapes of the goddesses. Through a digital approach, we can visualize the epigraphic data concerning ancient people, their ties with places, gods, and with each other. The charts and maps show the connectivity of distant places, such as Delos, Syrian Hierapolis, Athens, and Rome, and people of different cultural backgrounds who worshipped the goddesses. The database also lists the professions (capacities) of the worshippers, creating a platform for future study on the prosopography of ancient people, especially in the area of cults. This research highlights the importance of setting ancient people and their belief systems in their geographical and social contexts. Last but not least, it points to the necessity of ordering and cataloguing the dispersed epigraphic sources to explain the processes in ancient religions from the bottom-up approach.